Influence of the mechanical properties of the reactive Zr alloy liner on the multiple damaged effects post-target - Xinying Xue; Xingwei Liu; Shuang Liu; Jie Cao; Jinxu Liu (Journal of Materials Research and Technology)
We conduct a detailed investigation into the damage post-effects of Zr-based reactive liners on steel target under a 56 mm shaped charge caliber. The results demonstrate that when the Zr-based alloy serve as the reactive liner, under the condition of a small charge caliber, the penetration depth in the steel target can reach approximately 4 times the charge diameter (CD). Moreover, after penetrating a 100 mm thick steel target, the reactive residual jet and fragments can respectively detonate diesel and ignite combustibles located behind the steel target. Additionally, numerous fragments are generated during the interaction between the jet and the steel target, and these fragments penetrate a 3 mm thick post-effect Al target. Furthermore, simulations based on the Smoothed Particle Hydrodynamics (SPH) method are employed to explore the influence of mechanical properties on the damage post-effects of the reactive shaped charge liner (SCL). The fragments effectiveness is also evaluated. It is discovered that the jet dispersion and the formation of lethal fragments behind the main target are significantly influenced by the failure strain and yield strength of the SCL materials. During jet penetration, jets with lower yield and failure strains have a stress state approaching the failure state of the jet, which promotes fragment formation. However, fragments with high specific kinetic energy are more likely to be formed in SCLs with moderate failure strain and yield strength. The underlying mechanisms of jet dispersion and fragment formation after the jet penetrates the steel target are also elaborated in detail.